Effects of Karela (Bitter Melon; Momordica charantia) on genes of lipids and carbohydrates metabolism in experimental hypercholesterolemia: biochemical, molecular and histopathological study - Dalia Yossri Saad; Mohamed Mohamed Soliman; Ahmed A. Baiomy; Magdy Hassan Yassin; Hanan Basiouni El-Sawy (BMC, 2017)
Abstract Background Hypercholesterolemia is a serious diseases associated with type-2 diabetes, atherosclerosis, cardiovascular disorders and liver diseases. Humans seek for safe herbal medication such as karela (Momordica charantia/bitter melon) to treat such disorders to avoid side effect of pharmacotherapies widely used. Methods Forty male Wistar rats were divided into four equal groups; control group with free access to food and water, cholesterol administered group (40 mg/kg BW orally); karela administered group (5 g /kg BW orally) and mixture of cholesterol and karela. The treatments continued for 10 weeks. Karela was given for hypercholesterolemic rats after 6 weeks of cholesterol administration. Serum, liver and epididymal adipose tissues were taken for biochemical, histopathological and genetic assessments. Results Hypercholesterolemia induced a decrease in serum superoxide dismutase (SOD), catalase, reduced glutathione (GSH) and an increase in malondialdehyde (MDA) levels that were ameliorated by karela administration. Hypercholesterolemia up regulated antioxidants mRNA expression and altered the expression of carbohydrate metabolism genes. In parallel, hypercholesterolemic groups showed significant changes in the expression of PPAR-alpha and gamma, lipolysis, lipogenesis and cholesterol metabolism such as carnitine palmitoyltransferase-1 (CPT-1). Acyl CoA oxidase (ACO), fatty acids synthase (FAS), sterol responsible element binding protein-1c (SREBP1c), 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoAR) and cholesterol 7α-hydroxylase (CYP7A1) at hepatic and adipose tissue levels. Interestingly, Karela ameliorated all altered genes confirming its hypocholesterolemic effect. Histopathological and immunohistochemical findings revealed that hypercholesterolemia induced hepatic tissue changes compared with control. These changes include cholesterol clefts, necrosis, karyolysis and sever congestion of portal blood vessel. Caspase-3 immunoreactivity showed positive expression in hepatic cells of hypercholesterolemic rats compared to control. All were counteracted and normalized after Karela administration to hypercholesterolemic group. Conclusion Current findings confirmed that karela is a potential supplement useful in treatment of hypercholesterolemia and its associated disorders and is good for human health.